CHARITABLE AID TO CHILDREN IN EARLY 20TH CENTURY BAKU: THE ROLE OF NON-MUSLIM ORGANIZATIONS - Bagirova, Salala Vagif (History, Archeology and Ethnography of the Caucasus, 2025)
Research on charity, which gained prominence in the late 19th and early 20th centuries, has been documented in the scholarly works of Azerbaijani researchers such as N. Yakublu, L. Gadzhieva, S. Suleymanova, and F. Dzhabbarov. Furthermore, the topic of charity has been central to several dissertations, including S. Talibov’s “Cultural, Educational and Charitable Activities of the Azerbaijani Bourgeoisie, Late 19th – Early 20th Century”, M. Dzidzoev’s “Formation and Development of the Social Protection System in the North Caucasus in the Second Half of the 19th – Early 20th Century”, L. Ospishcheva’s “History of Charitable Organizations of Kuban, Late 19th – Early 20th Centuries”, and G. Ulyanov’s “Charity in the Russian Empire, Late 18th – Early 20th Century”). Notably, D. Dzhavadov, E. Dadashev, E. Dalgat, S. Gadzimagomedova, and T. Larionova have also presented findings on this subject at international conferences. Despite this body of work, the activities of non-Muslim children’s charitable organizations in Baku at the beginning of the 20th century remain largely understudied. This article addresses this gap by examining the activities and role of several significant charitable societies in Baku, drawing upon existing historiography and previously unpublished archival documents. The study emphasizes the role of the imperial family and the progressive Russian intelligentsia in organizing and supporting welfare for the poor and those facing hardship. In tracing the development of charitable activities, this article provides a chronology of this phenomenon within the Russian Empire, arguing that the establishment of charitable organizations received state-level support and their operations officially extended across the empire, including Northern Azerbaijan. The research indicates that charitable organizations focused on children’s health, education, and welfare effectively utilized available resources. Consequently, the strengthening of medical, health, and educational initiatives by these organizations positively influenced the reduction of negative issues associated with street children and children from impoverished families.